2004
DOI: 10.1172/jci19971
|View full text |Cite
|
Sign up to set email alerts
|

Bim regulation may determine hippocampal vulnerability after injurious seizures and in temporal lobe epilepsy

Abstract: Programmed cell death pathways have been implicated in the mechanism by which neurons die following brief and prolonged seizures, but the significance of proapoptotic Bcl-2 family proteins in the process remains poorly defined. Expression of the death agonist Bcl-2-interacting mediator of cell death (Bim) is under the control of the forkhead in rhabdomyosarcoma (FKHR) transcription factors. This prompted us to examine the response of this pathway to experimental seizures and in hippocampi from patients with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(87 citation statements)
references
References 55 publications
3
83
0
1
Order By: Relevance
“…Although Bim has three major isoforms generated by alternative splicing, namely Bim EL (extra-long), Bim L (long) and Bim S (short) (O'Connor et al, 1998), only Bim EL was detected as a single band at 23kDa in the rat hippocampus, consistent with a previous study (Shinoda et al, 2004).…”
Section: Ka Injurysupporting
confidence: 91%
See 1 more Smart Citation
“…Although Bim has three major isoforms generated by alternative splicing, namely Bim EL (extra-long), Bim L (long) and Bim S (short) (O'Connor et al, 1998), only Bim EL was detected as a single band at 23kDa in the rat hippocampus, consistent with a previous study (Shinoda et al, 2004).…”
Section: Ka Injurysupporting
confidence: 91%
“…Importantly, double labelling showed that Bim positive neurons were also TUNEL-positive, consistent with the notion that Bim is a pro-apoptotic protein in hippocampal neurons undergoing excitotoxic injury. Previous studies have shown an increase in number of Fluoro-Jade positive and TUNEL-positive degenerating pyramidal neurons 1 day after KA administration (Korhonen et al, 2003, Shinoda et al, 2004, and presence of activated caspase 3 in the hippocampus, 1 day after excitotoxic injury in mice (Theofilas et al, 2009). The results suggest greater vulnerability of neurons than microglia to apoptosis.…”
Section: Discussionmentioning
confidence: 65%
“…Upstream pro-apoptotic BH3 domain (Bcl-2 homology domain 3)-only members BAD (Bcl-2-associated death protein), Bid and Bim (Bcl-2-interacting mediator of cell death), can be activated via calcium-dependent mechanisms and each was found to be activated by seizures in vivo [11][12][13].…”
Section: Evidence Of Intrinsic Pathway Activation By Seizuresmentioning
confidence: 99%
“…SE induced Akt phosphorylation, a kinase that is regulated by PI3K, 30 min and 24 h after pilocarpine injection in WT, but not PI3Kγ −/− mice. Activation of Akt has been previously demonstrated in the hippocampus of patients with TLE and in the cortex of rats that received a kainic acid injection in the amygdala (Henshall et al, 2002;Shinoda et al, 2004). PI3Kγ is the only member of the family that can be activated by G protein coupled receptors.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have shown an increased Akt phosphorylation in the hippocampus of patients with temporal lobe epilepsy (Shinoda et al, 2004) and in the cortex of rats injected with kainic acid into the basolateral nucleus of the amygdala (Henshall et al, 2002). However, the role of PI3K in seizures, as well as in postictal events, is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%